Położenie prawne Międzynarodowego Banku Inwestycyjnego: [The legal situation of the International Investment Bank. A comparative study] (Studia Prawnicze / The Legal Studies, 2023)
Powstanie Międzynarodowej Banku Inwestycyjnego (MBI) jest ścisle związane z realizacja kompleksowego programu integracji gospodarczej krajów członkowskich Rady Wzajemnej Pomocy Gospodarczej. Autor przedstawia cele i funkcje MBI, klasyfikacje banków międzynarodowych, członkostwo, organy MBI i ich funkcje, strukturę organizacyjną niektórych Międzynarodowych Banków Rozwoju i Inwestycyjnych, formy prawne działalności MBI oraz podmiotowość prawnomiędzynarodową MBI.Jak wynika z powyższych rozważań MBI jest nowoczesną organizacją finansową o podobnych zasadach strukturalnych i działaniu jak inne tego typu instytucje międzynarodowe. Struktura banku i główne założenia są adekwatne do istniejących potrzeb rozwoju współpracy gospodarczej państw socjalistycznych. The establishment of the International Investment Bank (IIB) is closely linked to the implementation of the comprehensive economic integration programme of the member countries of the Council for Mutual Economic Assistance. The author presents the objectives and functions of the IIB, classifications of international banks, membership, IIB bodies and their functions, the organisational structure of some International Development and Investment Banks, the legal forms of IIB activities and the legal capacity of the IIB within international law. As the foregoing discussion shows, the IIB is a modern financial organisation with similar structural principles and operations to other such international institutions. The bank’s structure and main objectives are relevant to the existing needs of the development of economic cooperation of socialist states.